The combination of a neprilysin inhibitor (sacubitril) and angiotensin-II receptor blocker (valsartan) improves ejection fraction and longitudinal strain in mice treated with doxorubicin through NLRP3. (14th October 2021) - Quagliariello, V; Bonelli, A; Paccone, A; Buccolo, S; Iovine, M; Rea, D; Cerrone, F; Botti, G; Maurea, N
Abstract: Background: Doxorubicin-mediated- adverse cardiovascular events are among the leading causes of morbidity and mortality in breast cancer patients. Sacubitril-valsartan (LCZ 696) is a combination drug, made up of neprilysin inhibitor sacubitril and angiotensin II receptor blocker valsartan, used for the treatment of heart failure in patients with a reduced ejection fraction. Purpose: Here, we aim to assess whether LCZ 696, administered during doxorubicin, reduces in vitro anticancer drugs-related cardiotoxicity compared to Valsartan (V), used as a control drug. Methods: Human fetal cardiomyocytes (HFC cell line) were exposed to subclinical concentration of doxorubicin (at 200 nM) alone or in combination with LCZ-696 (100 mM) for 72 h. After the incubation period, we performed the following tests: determination of cell viability, through analysis of mitochondrial dehydrogenase activity, study of lipid peroxidation (quantifying cellular Malondialdehyde and 4-hydroxynonenal), intracellular Ca2+ homeostasis. Moreover, pro-inflammatory studied were also performed (activation of NLRP3 inflammasome; expression of TLR4/MyD88; mTORC1 Fox01/3a; transcriptional activation of p65/NF-κB and secretion of cytokines involved in cardiotoxicity (Interleukins 1β, 8, 6). C57Bl/6 mice were untreated (Sham, n=6) or treated for 10 days with doxorubicin (DOXO, n=6), LCZ-696 (LCZ, n=6) or doxorubicin combined to LCZ-696 (DOXO-LCZ, n=6). DOXO was injected intraperitoneally. Ejection fraction, radial and longitudinal strain were analyzed through transthoracic echocardiography (Vevo 2100). Cardiac tissue expression of NLRP3 inflammasome, Myd8, NF-kB and chemokines and cytokines were quantified after treatments through ELISA method. Results: LCZ 696 co-incubated with doxorubicin exerts cardioprotective effects, enhancing cell viability of 48–54.6% compared to only doxorubicin-treated cells (p<0, 001 for all); LCZ 696 reduced significantly the cardiotoxicity through MyD88/NF-KB/cytokines axis and mTORC1 Fox01/3α mediated mechanisms. In preclinical study, LCZ 696 improved significantly the EF and prevented the reduction of radial and longitudinal strain after 10 days of treatment with doxorubicin. A reduced expression of pro-inflammatory cytokines, NLRP3, MyD88 and NF-kB in heart tissues was also seen in DOXO-LCZ group compared to DOXO mice (p<0.001) Conclusion: We demonstrated, for the first time, that the LCZ696 exerts direct effects in cardiomyocytes and preclinical models during doxorubicin exposure, turning on a new light on its possible use in cancer patients to reduce cardiovascular side effects. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministero della Salute, Ricerca Corrente project